Public expenditure and optimal government size in an endogenous growth model: an analysis of the Argentine case - Rezk, Ernesto (2005)
In spite of the valuable contributions the Solow Swan Model rendered to the modern theory of Economic Growth the approach, based on a neoclassical production function with diminishing returns to labour and capital and combined with the assumption of a constant saving rate, yielded the uncomfortable prediction that per capita growth would eventually cease unless exogenous technological progress took place. By acknowledging this deficiency in the model, many theorists enriched the theory of Economic Growth in diverse ways; Cass (1965) and Koopmans (1965), for instance, resorted to Ramsey’s contribution to the analysis of consumer optimization in order to provide an endogenous determination of the saving rate. Let it however be said that this improvement of the neoclassical growth model did not solve the problem of dependence of the long run growth rate on exogenous technical advances. In aiming at sorting out the shortcomings of exogenous growth models, new lines of research, represented by the works of Romer (1986) and Lucas (1988), developed into what is known as endogenous growth models, allowing for a broader capital definition also including human capital and whose main feature was that the long run growth rate could be constant and possitive as diminishing capital marginal product did not take place . In following the latter line of analysis, it results interesting to consider the inclusion of government in endogenous growth models in order that questions of what the optimal government size and the tax rate maximizing per capita consumption, capital and income growth rates should be and what implications they will bear upon the analysis should one allow for distorting taxes to be used. In this connection the paper aims at identifying for Argentina, by using an AK endogenous growth model and resorting to taxes likely to alter incentives upon savings and investment, the government size that makes maximum the per capita growth rate. Furthermore, and whatever magnitude the estimation of government size may render, the empirical exercise carried out seeks to demonstrate that an inter temporal fiscal balance is possible if a more efficiency-oriented and better administered tax system is aimed at, free from distorting taxes and with respect to which existing evasion levels are curtailed.